Governing the egalitarians from without: The case of the internet - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2003)
Nobody would claim that regulators, or academics working on regulatory policy, have neglected the Internet. But most of this work is attracted by the global character of the Internet. Admittedly this is a serious challenge to regulation. But it is not the only, and probably not even the most disquieting challenge. One of the largely overlooked challenges to governance is cultural. The Internet originated in the egalitarian culture of American university computer labs. Its architecture has been shaped at the period. Up until now many key functions for Internet management are held by people coming from that culture. This paper basically makes three points: the egalitarian challenge to Internet governance has been largely overlooked. The challenge is serious, but not unmanageable. Yet regulators must use appropriate concepts to understand the challenge. A subfield of sociology, cultural theory, is particularly instrumental for that purpose. In order to address the challenge, regulators must use a set of governance tools that deviates considerably from standard regulatory responses. Governance can only be probabilistic, not deterministic. It must take into account that egalitarian movements are characterised by strong social embeddedness. It must address the cognitive and the belief side simultaneously. It must be aware of autopoiesis. It eventually must aim at restoring cultural balance.
Keywords: 330; Internet; Regulierung; Gerechtigkeit; Gleichberechtigung